Disembodied perspective: Third-person images in GoPro videos - Philippe Bédard (Alphaville: Journal of Film and Screen Media, 2015)
Used as much in extreme-sports videos and professional productions as in amateur and home videos, GoPro wearable cameras have become ubiquitous in contemporary moving image culture. During its swift and ongoing rise in popularity, GoPro has also enabled the creation of new and unusual points of view, among which are “third-person images”. This article introduces and defines this particular phenomenon through an approach that deals with both the aesthetic and technical characteristics of the images in question. An analysis is presented of the peculiar and unfamiliar appearance of third-person images, in which the head of the user remains fixed in space while the world around it moves independently. Technical descriptions are provided to explain why the perception of the world presented in third-person images differs so radically from our own “first-person” mode of perception. Throughout the article, descriptions and analyses of GoPro videos are supported by parallels to theories of movement and perception in the cinema, specifically Vivian Sobchack’s film phenomenology.